Satisfaction, engagement, and outcomes in internet-delivered cognitive behaviour therapy adapted for people of diverse ethnocultural groups: an observational trial with benchmarking - Sapkota, Ram P.; Valli, Emma; Dear, Blake F.; Titov, Nickolai; Hadjistavropoulos, Heather D. (Frontiers in Psychiatry, 2024)
Depression and anxiety are the most common mental health disorders worldwide. Internet-Delivered Cognitive Behaviour Therapy (ICBT) can reduce barriers to care to broad cross sections of the population. However, People of Diverse Ethnocultural Backgrounds (PDEGs) other than White/Caucasian underutilize mental health services and are under represented in clinical trials of psychological interventions. To address this research gap we adapted an evidence-based ICBT program for PDEGs. The current pilot study explores the engagement, satisfaction, and effectiveness in the adapted ICBT program by PDEGs (N=41) when benchmarked against a sample of PDEGs (N=134) who previously completed a non-adapted version of the ICBT program. An intent-to-treat analyses showed that the adapted ICBT program is effective in reducing anxiety and depression symptoms among PDEGs. Large within-group pre-to-post-treatment Cohen's effect sizes of d = 1.23, 95% CI [0.68, 1.77] and d = 1.24, 95% CI [0.69, 1.79] were found for depression and anxiety, respectively. Further, 81.8% of the PDEGs who received the adapted ICBT reported overall satisfaction, 90.9 % reported increased confidence in managing symptoms, and 70.7% completed majority of the psychoeducational lessons in the ICBT program. No statistically significant differences in the clinical outcomes, engagement, and satisfaction were found between the pilot study and benchmark sample. Future directions for ICBT research with PDEGs are described.